CYBERCRIME AWARENESS ON ONLINE SHOPPING AMONG UITM STUDENTS AT TERENGGANU CAMPUS - Ahmad, Nor Faezah Ghazi; Mohd Rosly, Nuurul Farihah (Jurnal 'Ulwan, 2024)
In recent decades, the Internet has emerged as an essential element of our daily lives. The widespread reliance of individuals on the internet has substantially increased their vulnerability to cybercrime. The prevalence of cybercrime has become a substantial peril in modern society. This research aimed to examine the variables that are associated with the extent of cybercrime awareness among students enrolled at UITM Dungun. To achieve the objective, the research was centered on particular research objectives, which entailed examining the attributes of social media that influence the degree of cybercrime awareness among students enrolled at UiTM Terengganu. As a result, 116 students in total contributed to the successful completion of the research. The Statistical Package for the Social Sciences (SPSS Statistic 28.0.1.1 Windows) was utilised to gather the data. According to the results of this research, a considerable percentage of students demonstrated awareness and understanding of the concept of cybercrime. There is broad consensus regarding the substantial surge in cybercrime. In contrast, this issue can be effectively mitigated through the implementation of appropriate preventive measures. Users are advised to exercise caution when accessing the internet. The documentation and observation of students can be achieved by conducting a range of educational activities, including seminars, workshops, and conferences.